The G20 and the 2030 Agenda for Sustainable Development Sustainable Development: How to strengthen policy coherence and accountability - Marianne Beisheim (Stiftung Wissenschaft und Politik (SWP), 2017)
The next G20 Summit will take place in Hamburg on 7/8 July 2017. Under the Chinese Presidency, the G20 adopted the Action Plan on the 2030 Agenda for Sustainable Development at the 2016 Summit in Hangzhou. The 2030 Agenda had been signed by heads of state and government during the United Nations (UN) General Assembly in 2015. The German Presidency is now planning a 'Hamburg update' of the G20 Action Plan. What kinds of contributions from G20 countries could boost the implementation of the ambitious 2030 Agenda? How can the G20 and UN processes be meaningfully linked, particularly with regard to policy coherence and accountability measures? (SWP Comments)
Keywords: 320